Arterial stiffness after 6 weeks postdelivery in women with a history of hypertensive disorders of pregnancy: a systematic review and meta-analysis - Mbongozi, Xolani B.; Galloway, Stuart D. R.; Hunter, Angus M.; Milambo, Jean Paul M.; Businge, Charles B. (Frontiers in Medicine, 2025)
IntroductionThe main objective of this systematic review was to determine if the arterial stiffness remains elevated after 6 weeks post-delivery in women with a history of hypertensive disorders of pregnancy (HDP).Methods and analysisA comprehensive systematic literature search was conducted across multiple electronic databases, including Medline, PubMed, Embase, Cochrane Library, Google Scholar, Web of Science, and CINAHL. We included studies assessing arterial stiffness in women with a history of HDP between 43 days and 10 years postdelivery, with participants under 60 years of age. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) guidelines. We extracted data on arterial stiffness indices, including carotid-femoral pulse wave velocity (cfPWV), augmentation index (AIx), and heart rate adjusted augmentation index (AIx@75), along with the mean ± standard deviation for each study. A random-effects model was used to pool data, and heterogeneity was explored through sensitivity and subgroup analyses. The Newcastle Ottawa Scale (NOS) and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) were used to assess risk of bias and quality of evidence.ResultsOut of 121 identified articles, 12 studies involving a total of 856 women were included in the final review after eliminating duplicates and irrelevant studies. The overall pooled data revealed a significantly elevated AIx and cfPWV among women with a history of HDP. Specifically, the mean difference (MD) in AIx was 11.63 (95% Confidence Interval (CI): [1.72–21.54]), and for cfPWV, the MD was 0.53 (95% CI: [0.27–0.78]). Notably, while AIx showed no significant change in women within 1 year postpartum (MD 14.85, 95% CI [−6.03–35.72]), an elevation was observed in those beyond 1 year post-delivery (MD 9.11, 95% CI [4.20–14.02]). cfPWV was also found to be elevated in HDP patients both within 1 year (MD 0.59, 95% CI [0.32–0.86]) and beyond 1 year (MD 0.45, 95% CI [0.03–0.88]). In cases of early-onset preeclampsia, AIx did not show a significant increase; however, a significant increase in cfPWV was observed, with AIx having an MD of 1.55 (95% CI: [−0.74–3.84]) and cfPWV an MD of 1.86 (95% CI: [0.25–3.47]). For late-onset preeclampsia, there was no significant difference in AIx (MD 2.44, 95% CI: [−8.82–13.70]) or cfPWV (MD 0.10, 95% CI: [−0.42–0.62]).ConclusionThis systematic review and meta-analysis suggest that arterial stiffness may remain elevated beyond 6 weeks postpartum in women with a history of HDP. However, the findings should be interpreted with caution due to heterogeneity across studies and limited number of available studies. Larger and standardized longitudinal studies are needed to confirm these results. In the meantime, regular cardiovascular monitoring for these women is recommended while awaiting more conclusive evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/search, CRD42023461867.